Translating GWAS Findings to Novel Therapeutic Targets for Coronary Artery Disease - Shu, Le; Blencowe, Montgomery; Yang, Xia (Frontiers in Cardiovascular Medicine, 2018)
The success of genome-wide association studies (GWAS) has significantly advanced our understanding of the etiology of coronary artery disease (CAD) and opens new opportunities to reinvigorate the stalling CAD drug development. However, there exists remarkable disconnection between the CAD GWAS findings and commercialized drugs. While this could implicate major untapped translational and therapeutic potentials in CAD GWAS, it also brings forward extensive technical challenges. In this review we summarized the motivation to leverage GWAS for drug discovery, outlined the critical bottlenecks in the field, and highlighted several promising strategies such as functional genomics and network-based approaches to enhance the translational value of CAD GWAS findings in driving novel therapeutics.